2005
DOI: 10.1017/s0265021503000899
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of two intrathecal anaesthetic techniques for transurethral prostatectomy on haemodynamic and pulmonary function

Abstract: The addition of fentanyl 25 microg to bupivacaine 10 mg and limiting the spread of the block does not improve either haemodynamic or pulmonary function compared with bupivacaine 15 mg in patients undergoing transurethral prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Trials were published between 1992 and 2012 and included data on 1393 patients, 733 of whom received intrathecal opioids (Table 1) [1,[3][4][5][6][7][8][11][12][13][14]22,[24][25][26][27]29,30,32,34,35,38,39,[42][43][44][45][46]. The median group size was 20 patients (range, 10-60 patients).…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trials were published between 1992 and 2012 and included data on 1393 patients, 733 of whom received intrathecal opioids (Table 1) [1,[3][4][5][6][7][8][11][12][13][14]22,[24][25][26][27]29,30,32,34,35,38,39,[42][43][44][45][46]. The median group size was 20 patients (range, 10-60 patients).…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…In the other 17 reports, there was a large variety of working hypotheses: different analgesic efficacy and different risks of adverse effects with experimental interventions [1,3,8,11,14,26,32,44]; improved analgesia and fewer adverse effects [13,25]; improved analgesia and equal risk of adverse effects [30]; equal analgesia and equal risk of adverse effects [22]; fewer adverse effects with no statement about analgesic efficacy [6,29,45]; and improved analgesia and potentially increased risk of adverse effects [27,35]. Selection of the LA dose in controls was based on literature findings in 6 reports [7,12,26,38,43,45], on previous personal findings in 2 [24,29], but unclear in the remaining 18 (64%).…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous investigation in patients undergoing transurethral resection of the prostate demonstrated that lung function was not altered when fentanyl was added to bupivacaine for spinal anesthesia. 24 Although fentanyl might reduce respiratory drive, it would be unlikely to affect capacity.…”
Section: Discussionmentioning
confidence: 99%